Association between general anesthesia and contrast-induced encephalopathy after endovascular treatment on neurovascular diseases - Zhong, Zhihong; Ni, Hongyang; Zhu, Jun; Jiang, Hong; Hu, Jinqing; Lin, Dong; Bian, Liuguan (Frontiers in Neurology, 2023)
Objective Contrast-induced encephalopathy (CIE) is a rare neurological complication that can occur in the context of various endovascular procedures. Although many potential risk factors for CIE have been reported, it is still unclear whether anesthesia is a risk factor for the occurrence of CIE. The goal of this study was to investigate the incidence of CIE in patients who underwent endovascular treatment under different anesthesia methods and anesthetics administration and to explore whether general anesthesia was a potential risk factor for CIE. Methods We retrospectively reviewed available clinical data from 1,043 patients with neurovascular diseases undergoing endovascular treatment between June 2018 and June 2021 in our hospital. A propensity score-based matching strategy and logistic regression were used to analyze the association between anesthesia and the occurrence of CIE. Results In this study, we implemented the embolization of intracranial aneurysm in 412 patients, stent implantation of extracranial artery stenosis in 346, stent implantation of intracranial artery stenosis in 187, embolization of cerebral arteriovenous malformation or dural arteriovenous fistula in 54, endovascular thrombectomy in 20, and other endovascular treatments in 24. A total of 370 patients (35.5%) received treatment under local anesthesia, while the remaining 673 (64.5%) underwent treatment under general anesthesia. In total, 14 patients were identified as CIE, resulting in a total incidence rate of 1.34%. After propensity score-based matching of anesthesia methods, the occurrence of CIE was significantly different between the general anesthesia and local anesthesia group (P = 0.007). After propensity score-based matching of CIE, the anesthesia methods were significantly different between the two groups. Pearson contingency coefficients and logistic regression showed a significant correlation between general anesthesia and the risk of CIE. Conclusion General anesthesia might be a risk factor for CIE, and propofol might be associated with the increased occurrence of CIE.